METODE KONSELING QUR’ANI DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA DISEKOLAH (STUDI PENELITIAN KUALITATIF) - Diningsih, Fitri; Yulia, Cici (LPPM Institut Pendidikan Nusantara Global, 2023)
This study intends to understand whether there is an impact of individual counseling on increasing faith in the holy Qur'an in grade 8 students of SMPN 3 PAMARAYAN during semester 2 of the 2022 - 2023 school year or not. The method used is descriptive qualitative research method by collecting data through observation, question and answer, and documents about subjects and subjects of SMP Negeri 3 PAMARAYAN. Based on the results of observations made by researchers, they undergo observation (exploration) and question and answer. Analysis of the results obtained by researchers was then carried out with field tests and activity documentation, after which the researchers concluded with individual consulting services to develop students' self-confidence. Individual counseling services are provided when students' problems can affect student performance in learning and dealing with their environment, often causing embarrassment to students. Like those with low capacity, students with low self-esteem tend to mingle less with their peers and play less of a role in learning because they realize that it is not appropriate to make assumptions and often realize that what they are doing is wrong and very embarrassing when in class. From the results of this observation, it can be found that if there is no excessive psychological impact on the counselee, what must be done is to organize a BMB3 consultant so that the counselee can manage his daily activities as well as possible and tends to follow a good structure.